Comparison of the Donor Age-Dependent and In Vitro Culture-Dependent Mesenchymal Stem Cell Aging in Rat Model - Katarzyna Siennicka; Aleksandra Zołocińska; Tomasz Dębski; Zygmunt Pojda (Hindawi Limited, 2021)
Clinical experiments suggest that mesenchymal stem cells (MSCs) may be useful for tissue repair therapies or treatment of the autoimmune disorders. There is still lack of consensus concerning the age limit of MSC donors, majority of researchers suggest the autologous MSC therapies of patients not exceeding age limit of 55-60 yrs. The purpose of our study was to compare the selected parameters of MSCs from adipose tissue (adipose stem cell, ASC) collected from young and old rats of ages corresponding to patient's ages 25 yrs. and 80 yrs., respectively. The differences of parameters of ASCs from young and old animals were compared with the differences between ASCs from short-term (3 passage) and long-term (30 passage) in vitro culture. Cell morphology, surface marker expression, growth potential, metabolic activity, β-galactosidase activity, clonogenic potential, angiogenic potential, and differentiation ability of ASCs from young and aged animals and from in vitro cultures at 3rd and 30th passages were compared and analyzed. It may be concluded that ASCs may be applied for autologous transplantations in aged patients. Comparison of ASC aging dynamics depending on host aging or in vitro culture duration suggests that long-term in vitro culture may affect ASCs more than natural aging process of their host. We suggest that ASCs expanded in vitro prior to their clinical use must be carefully screened for the possible aging effects resulting not only from donor age, but from the duration of their in vitro culture.